Exploring Acehnese EFL College Students’ Perceptions on Collaborative Writing - Zulfikar Zulfikar; Cut Tarri Aulia (LPPM Universitas Bina Sarana Informatika, 2020)
Applying collaborative approaches in teaching writing has been shown to have a myriad of advantages. Most of the studies on collaborative writing in language teaching, however, have focused on second language rather than foreign language contexts. This study investigated perceptions of Acehnese EFL college students toward the implementation of collaborative writing in their EFL classrooms at Ar-Raniry State Islamic University, Banda Aceh, Indonesia. The general design of the research was qualitative in nature since the study used narrative inquiry as the research instrument and emphasized on each participant’s learning experiences with collaborative writing strategy. In order to understand the participants’ perceptions of collaborative learning, the researcher observed, took notes and recorded each of their interview responses. The overall results revealed that collaborative writing was perceived as beneficial for not only improving accuracy and clarity of the EFL students’ writing, but also providing the opportunity for them to pool their ideas, reduce their apprehension, and increase their self-confidence. Results also showed that the EFL students believed that collaborative project writing was not always feasible due to their different writing style, social loafing, as well as time pressure. These findings could function as important intellectual resources for more effective collaborative writing implementation. The study concludes with recommendations for further pedagogical explorations on different aspects of collaborative writing in EFL context in the future.